Respostas
respondido por:
0
Encontrar a razão da PA:
r = a2 - a1
r = 11 - 7
r = 4
===
an = a1 + ( n -1 ) . r
a9 = 7 + ( 9 -1 ) . 4
a9 = 7 + 8 . 4
a9 = 7 + 32
a9 = 39
===
an = a1 + ( n -1 ) . r
a17 = 7 + ( 17 -1 ) . 4
a17 = 7 + 16 . 4
a17 = 7 + 64
a17 = 71
r = a2 - a1
r = 11 - 7
r = 4
===
an = a1 + ( n -1 ) . r
a9 = 7 + ( 9 -1 ) . 4
a9 = 7 + 8 . 4
a9 = 7 + 32
a9 = 39
===
an = a1 + ( n -1 ) . r
a17 = 7 + ( 17 -1 ) . 4
a17 = 7 + 16 . 4
a17 = 7 + 64
a17 = 71
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás